Modeling of Cloud Surveillance System - Diatlov, Ie.I. (Математичні машини і системи, 2016)
The article is devoted to the Cloud Surveillance. The author describes global distributed structure of surveillance system and its main components. The article highlights the main points concerning the processing of video and distributed data storage model. The paper describes main abilities to spread the load among equivalent system services. The author underlines the importance of database replications and backup. This article describes the basic service delivery models of data centers and their positioning relative to the cloud video surveillance applications.